Whole body imaging using 18-Fluorine Fluorodeoxyglucose (18F-FDG) Positron Emission Tomography/Computed Tomography (PET/CT) with or without contrast enhanced computed tomography (CT) in dignosing arteritis - Nordin, Abdul Jalil; Abdul Rahim, Noraini; Rossetti, Claudio; Lind, Peter; Kresnik, Ewald (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2009)
Introduction: Takayasu’s Arteritis and Horton’s Arteritis are two rare cases of autoimmune complex diseases resulting in sterile inflammatory reactions affecting the wall of large and medium sized arteries. Various radiological and interventional methods employed are inconclusive and become diagnostic only when complications begin to set in. The new non-invasive hybrid Positron Emission Tomography Computed Tomography (PET/CT) using 18Florine-Fluorodeoxyglucose (18F-FDG) imaging technique could detect arteritis in an early clinical stage when routine conventional cross-sectional imaging was inconclusive. Method: Two cases from Klagenfurt Hospital, Austria and Milan General Hospital, Italy were compared with image acquisition being done in the respective hospitals. In Klagenfurt, PET/CT image acquisition was performed using intravenous contrast administration and in Milan, CT parameters were used as attenuation correction and anatomical correlation of PET images. Results: CT performed using both methods, with or without iodinated contrast media, were useful in detecting arteritis. Conclusion: It is concluded that PET/ CT aside from being a useful tool in cancer imaging, is also useful for pyrexia of unknown origin. PET/CT should be employed early in managing this clinical condition where arteritis is a possible diagnosis.